Defining vascular anomaly phenotypes in children based on a systematic literature search: A critical step in developing a single severity score for interventional clinical trials. Issue 10 (20th July 2022) - Gariépy‐Assal, Laurence; Dubois, Josée; Zwicker, Kelley; Pincivy, Alix; Powell, Julie; Zhang, Yang; Breakey, Vicky; Price, Victoria; Brandão, Leonardo R.; Carcao, Manuel; Kleiber, Niina
Abstract: Introduction: Genetically targeted drugs in vascular anomalies (VA) are used despite the absence of a validated severity score. The aim of this study was to evaluate the feasibility of grouping phenotypic VA clinical characteristics into a single severity score. Methods: A systematic literature review including children treated with sirolimus accompanied by a detailed description of phenotype and management was conducted. Demographic data and clinical features were extracted to define distinct categories of phenotypes. Results: Children with VA display two main phenotypes regardless of VA subtype, which may overlap. A systemic phenotype results from direct invasion and compression of vital structures generally leading to hospitalization and aggressive management in infancy. A functional phenotype is associated with chronic pain and disability manifesting mainly during early adolescence and managed in the outpatient setting. Conclusion: The two distinct phenotypes described could be the basis for developing a unified scoring system for VA severity assessment.